Examining the predictors of teachers’ organisational citizenship behaviour from an individual perspective: the role of human values – benevolence, achievement, self-direction and conformity - Gnanarajan, A.H.; Kengatharan, N. (Taylor & Francis Group, 2022)
Organisational citizenship behaviour (OCB) of teachers has been found essential for the effective functioning of schools, and tea-chers’ propensity to perform OCB is determined by various indivi-dual and organisational characteristics. The present study investigates the role of human values – benevolence, achieve-ment, self-direction and conformity – in OCB in a sample of teachers. The study model was examined with structural equation modelling using AMOS. Data were collected using self-report questionnaires from 410 teachers in the secondary schools in Sri Lanka. The results revealed that, of the four values examined, benevolence correlated significantly with OCB, while achieve-ment, self-direction and conformity had no significant relationship with OCB. The present study contributes to the growing empirical research on teacher’s OCB and offers practical recommendations for principals and educational administrative authorities, and the-oretical implications and recommendations for future studies
Keywords: Organisational citizenship Behaviour; Human values; Schools; Teacher’s OCB